A gourmetização como fenômeno mediático: uma análise dos processos de estetização do cotidiano por meio de práticas comunicacionais e de consumo com a gastronomia - Oliveira, Caroline Cavalcanti de (2018)
In a communicational perspective the research addresses processes of aesthetization of daily life associated with media projection and consumption of gastronomy, and its resulting relations with contemporary conceptions of taste. Once an aesthetic interest is identified in the circulation of contents, particularly related to the act of cooking, it is analyzed to what extent social actors (especially the subjects, the industry, the market and the media), by means of communicational practices and consumption logics, manifest an aesthetic disposition with the current conception of gastronomy (which has cooking as an axis of interest) and carry out a communicational appropriation of the kitchen. The thesis is that with the process of mediatization of gastronomy and the prestige of aesthetic dimensions in communicational practices and consumption protocols, a phenomenon of gourmetization based on the qualification of the act of cooking emerges as a way of aestheticizing everyday life. The adopted conception of aesthetization involves threads of the sensible, incitement to aesthetic experience and aspects of artification. As a starting point, the research contemplates the established relation of mirroring between media and everyday practices, considering the interactions, the communicational strategies and the processes of styling and design as agents of a process of mediatizaton of gastronomy. In the observed scenario, it is understood that the terms gourmet and chef, and related forms of expression, act as mechanisms of aesthetization concerning brands, products, services, contents, spaces, materialities of the media and also the subjects. Therefore, one analyzes materialities corresponding to the conception of gastronomy as an organization of a significant discourse, of an aesthetic character, in the qualification of the daily life elements. The theoretical approach is based on aesthetics of communication, using sociossemiotics and cultural studies (particularly the food studies), associated with phenomenology to address the proposed analysis. The research is exploratory and qualitative, with multiple case studies that compose the investigated object, which enables the perception of a mediatic phenomenon, of an aesthetic-communicational character. An unsystematic non-participant observation with documental and bibliographical researches and interviews is carried on, bringing up communicational analyzes in aesthetic perspective. As a result, it is understood that with the expansion of practices and spaces there is an overflow of gourmetization. Since the context has substantially affected everyday life, in addition to the adoption of a lifestyle its developments suggest the organization of a culinary-gastronomic culture.